2014
DOI: 10.1039/c4tb01385a
|View full text |Cite
|
Sign up to set email alerts
|

Convenient and sensitive detection of norfloxacin with fluorescent carbon dots

Abstract: Carbon dots (CDs) were synthesized by refluxing glucose, as efficient fluorescence probes, which show convenient and sensitive detection of norfloxacin (NOR) over a wide concentration range. It is worth noting that because of the hydrogen bond interactions between the CDs and NOR, the fluorescence intensity of CDs was remarkably enhanced in the presence of NOR, which indicates that CDs are capable of rapid, stable and sensitive determination of NOR. Compared with high-performance liquid chromatography, the flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 42 publications
1
59
0
Order By: Relevance
“…Meanwhile, it can be clearly seen that the maximum emission intensity was centered at 354 nm with an excitation wavelength of 280 nm. Moreover, the synthesized CDs exhibited excitationdependent fluorescence behavior which was similar as previous reports on CDs [40,41]. As shown in Fig.…”
Section: Characterization and Fluorescence Of The Cdssupporting
confidence: 84%
“…Meanwhile, it can be clearly seen that the maximum emission intensity was centered at 354 nm with an excitation wavelength of 280 nm. Moreover, the synthesized CDs exhibited excitationdependent fluorescence behavior which was similar as previous reports on CDs [40,41]. As shown in Fig.…”
Section: Characterization and Fluorescence Of The Cdssupporting
confidence: 84%
“…Additionally, in comparison with that of the ternary systems, CPEN/BA‐ph/CE prepolymer shows larger viscosity after 2500 s at 200 °C than that of BA‐ph/CE/CPEN, indicating that the methods of introducing CPEN also affect the curing behaviors. This can be explained by the fact that for CPEN/BA‐ph/CE prepolymer, CPEN was mixed with BA‐ph/CE for 3 h, the molecular chains of CPEN can disperse homogeneously in the BA‐ph/CE; more importantly, the nitrile groups in molecular chains of CPEN when mixed with BA‐ph/CE for 3 h, would obtain more opportunities to interact with BA‐ph/CE to form the network, thereby, showing a little larger viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…confirmed that the introduction of PEN containing hydroxyl groups into the phthlonitrile matrix can improve the interface between GF and polymer matrix. However, in the previous work, PEN resins are very difficult to form crosslink network without the catalysts because of steric hindrance of the pendant nitriles groups on the polymer chains and the high curing temperature (>300 °C) have enormously limited the application of the reinforced composites …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, doped carbon nanodots synthesized by bottom up methods have been researched extensively due to the simplicity in preparation 16 and significant improvement in optical performance including quantum yield and optical tunability 17,18 . As a consequence of doped CDs' versatility, they have been studied for wide range of applications including biological imaging [19][20][21][22] , light harvesting 23 39 have been successfully demonstrated.…”
Section: Introductionmentioning
confidence: 99%